2014
DOI: 10.1071/sr13100
|View full text |Cite
|
Sign up to set email alerts
|

Digital mapping of a soil drainage index for irrigated enterprise suitability in Tasmania, Australia

Abstract: An operational Digital Soil Assessment was developed to inform land suitability modelling in newly commissioned irrigation schemes in Tasmania, Australia. The Land Suitability model uses various soil parameters, along with other climate and terrain surfaces, to identify suitable areas for various agricultural enterprises for a combined 70 000-ha pilot project area in the Meander and Midlands Regions of Tasmania. An integral consideration for irrigable suitability is soil drainage. Quantitative measurement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…This could introduce inconsistency between datasets and potential modelling errors. Kidd et al (2014a) drew attention to the problem of data inconsistency in relation to soil drainage, and proposed the use of a soil drainage index that combines field-allocated site-drainage classes with quantitative DSM methods to produce enhanced soildrainage surfaces. Another problem associated with the wetness limitation evident in this project is that based on field descriptions, soil sites tend to be clustered in a limited number of site-drainage classes that do not adequately differentiate between the different agronomic requirements of specific crops.…”
Section: Discussionmentioning
confidence: 99%
“…This could introduce inconsistency between datasets and potential modelling errors. Kidd et al (2014a) drew attention to the problem of data inconsistency in relation to soil drainage, and proposed the use of a soil drainage index that combines field-allocated site-drainage classes with quantitative DSM methods to produce enhanced soildrainage surfaces. Another problem associated with the wetness limitation evident in this project is that based on field descriptions, soil sites tend to be clustered in a limited number of site-drainage classes that do not adequately differentiate between the different agronomic requirements of specific crops.…”
Section: Discussionmentioning
confidence: 99%
“…RFM model helps prediction of land degradation such as alkalinity from the predicted soil maps (Vågen et al, ), and knowledge of the desertification process at a particular location is effectively captured, we can able to extrapolate to surrounding areas based on spatial correlation of available predictors. The training site relies on surveyor experience and local landscape knowledge (Kidd et al, ). The information needed to train classification algorithms can be obtained for training areas through ground truth verification for quickly updating DSM maps at frequent time intervals by using this methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The information needed to train classification algorithms can be obtained for training areas through ground truth verification for quickly updating DSM maps at frequent time intervals by using this methodology. A another advantage of the RFM model that this model can be applied to any legacy data having desertification/land degradation processes to derive either new maps or to improve existing mapping (Kidd et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…347). Campling et al (2002) reported a κ of 0.705, Kidd et al (2014) found κ values of 0.27 and 0.31 for the two study regions, Lemercier et al (2012) reported a κ of 0.27 and Peng et al (2003) found a κ of 0.59 for predictions of three drainage levels. The κ values computed for the models of this study ranged between 0.37 and 0.5 for modelling the presence of waterlogged horizons and was 0.48 for predicting the three levels of drainage class.…”
Section: Predictive Performance Of Fitted Modelsmentioning
confidence: 99%
“…Three studies with up to seven drainage levels achieved PC of 52 to 78 %, and Zhao et al (2013) had 36 % of correctly classified sites. Kidd et al (2014) found PC of 53 and 55 % for two study regions, and Lemercier et al (2012) reported PC of 52 % for a four-level drainage response. The presented models (Table 4 and 5) are almost as good with PC of 78 to 82 % for predicting the presence of waterlogged horizons and PC of 78 % for predicting the three drainage class levels.…”
Section: Predictive Performance Of Fitted Modelsmentioning
confidence: 99%